Investing in Children, Youth, Families, and Communities: Strengths-Based Research and Policy. 2004
DOI: 10.1037/10660-004
|View full text |Cite
|
Sign up to set email alerts
|

Strengths-building public policy for children of divorce.

Abstract: This research was supported by National Institute of Mental Health grant P30 MH439246-16. 'A related adverse circumstance is nonmarital childbirth, which is almost as common (35.8 % versus 37.0% of children living in divorced homes; Bureau of the Census, 1996) and perhaps even more toxic. This chapter is confined to children whose parents were once legally married and subsequently experienced divorce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…After a thorough review of the empirical research literature, Grych (2005) concluded that prevention programs designed to improve parent‐parent relationships after divorce should be a part of the menu to protect children from the negative effects associated with divorce. Integrating proven programs for divorcing families into family courts is the next challenge facing preventionists (Braver, Hipke, Ellman, & Sandler, 2004). Our results suggest that Dads for Life presented to volunteering fathers offers substantial promise to courts hoping to alter the trajectories of divorcing families.…”
Section: Resultsmentioning
confidence: 99%
“…After a thorough review of the empirical research literature, Grych (2005) concluded that prevention programs designed to improve parent‐parent relationships after divorce should be a part of the menu to protect children from the negative effects associated with divorce. Integrating proven programs for divorcing families into family courts is the next challenge facing preventionists (Braver, Hipke, Ellman, & Sandler, 2004). Our results suggest that Dads for Life presented to volunteering fathers offers substantial promise to courts hoping to alter the trajectories of divorcing families.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the domestic relations court has considerable authority to impact parents' and children's lives (Braver, Cookston, & Cohen, 2002). Fourth, in recent years, domestic relations courts have developed an array of nonjudicial programs to improve the well-being of parents and children in divorced families (Braver, Hipke, Ellman, & Sandler, 2004), including brief, often mandatory, parent informational programs, which could be used to recruit parents into longer, more intensive programs. Finally, a recent survey of court-based service providers demonstrated the feasibility of delivering programs like the NBP in the courts (Cookston, Braver, Sandler, & Genalo, 2002).…”
Section: Nbp: Steps From Efficacy To Effective Implementation In the mentioning
confidence: 99%
“…For example, an emotionally close relationship with a supportive and authoritative father has been shown to relate to child well-being (Amato & Gilbreth, 1999). Moreover, the factor with the greatest importance for the child's adaptation is the degree of conflict between the parents postdivorce (Amato & Keith, 1991;Braver, Hipke, Ellman, & Sandler, 2004); fathers are one of the two parents who conjointly create this conflict. Thus, there is a plausibly considerable benefit to children that will accrue by a preventive program designed to work with fathers.…”
Section: Prevention With Nonresident Fathers: Considerations From Thementioning
confidence: 99%